Exploring active learning patterns of technical and vocational education training students in practical activities based on internet of things - Jalani, Eddy Azhar; Omar, Muhd Khaizer; Perumal, Thinagaran (Human Resources Management Academic Research Society (HRMARS), 2023)
This concept paper discusses the initial idea of exploring the active learning pattern of technical and vocational education students in practical activities based on the Internet of Things. The Internet of Things is a new technology that is one of the pillars of the 4th industrial revolution. The acceptance of students in this new technology raises several questions, namely how the active learning pattern of students who develop skills in practical activities based on the Internet of Things, how current student strategies develop skills in practical activities based on the Internet of Things and what is the state of transition of skill development strategies in practical activities based on the Internet of Things. The study in the form of a case study was attempted by the researcher using content analysis and sequential analysis to explore the active learning pattern of students. The active learning that will be implemented by the students is by giving them a task to build a control system by using Internet of Things technology. It is well known that in building a control system by using internet technology, various micro control objects are used which are mostly based on open source and students are free to explore in developing this system. This exploration is important to see the learning pattern that results when students do this practice. The findings of this study can suggest an active learning towards forming better skills and sustainability.